Biomechanical Comparison of Deep Water and Treadmill Running - Mercer, J. A.
The purpose of this project was to determine whether or not the running strategy observed during DWR was similar to the running strategy utilized during treadmill running (TMR). An analysis will be made of the temporal relationships of the ankle, knee and hip joints during DWR and TMR of an experienced runner (on land and in deep water). Additionally, muscle activity level of the rectus femoris (quadriceps) and biceps femoris (hamstring) will be compared between the two modes of exercise. These variables will allow for a quantitative comparison of mechanics of running between modes of exercise. If DWR and TMR running are similar mechanically, the practitioner should be confident that benefits of a DWR training program will likely transfer to land based measures of performance (e.g. TMR). If the running styles are different during the two modes of exercise, then it would seem that the practitioner should encourage individuals to incorporate land based exercise when tolerable. Presently, the data from one subject have been collected and analyzed. This phase of the project is exploratory. Because of the lack of biomechanical data comparing DWR and TMR, this phase of the project will be used to identify important variables that allow for a quantitative comparison of running mechanics between modes of exercise.